Novel therapeutic agents for the treatment of diabetic kidney disease. (1st November 2020) - Hartman, Rachel E.; Rao, P.S.S.; Churchwell, Mariann D.; Lewis, Susan J.
ABSTRACT: Introduction: Diabetic kidney disease (DKD) involves multifaceted pathophysiology which increases the risk of cardiorenal events and mortality. Conventional therapy is limited to renin-angiotensin aldosterone system inhibition and management of hyperglycemia and hypertension. Recent clinical trials have demonstrated promising nephroprotective effects of antihyperglycemic agents thus modifying guideline treatment recommendations for type 2 diabetic patients with chronic kidney disease. Areas of covered: Relevant studies and clinical trials were searched via PubMed and clinicaltrials.gov through August 2020. Authors offer an update on clinical evidence regarding nephroprotective effects and side effects of sodium-glucose-cotransporter-2 (SGLT2) inhibitors, glucagon-like-peptide-1 (GLP1) agonists and dipeptidylpeptidase-4 (DPP4) inhibitors. They discuss the potential benefits of novel therapy targeting DKD pathogenic processes including inflammation, oxidative stress, fibrosis, and vasoconstriction shown in early phases of clinical trials and offer an opinion on key challenges and directions for future progress. Expert opinion: SGLT2 inhibitors are the most promising agents for DKD and improving cardiorenal outcomes. Mineralocorticoid-receptor antagonists and janus kinase inhibitors are also promising investigational therapies that target oxidative stress, nitric oxide synthesis, and inflammation. Novel therapeutic targets and the identification of clinically useful biomarkers may provide future therapies that detect early stages of DKD enabling a slower kidney function decline.